A Latent Factor Model with Global, Country, and Industry Shocks for International Stock Returns - Del Negro, Marco; Brooks, Robin (Washington, D.C. : International Monetary Fund, 2005)
We estimate a latent factor model that decomposes international stock returns into global, country-, and industry-specific shocks and allows for stock-specific exposures to these shocks. We find that across stocks there is substantial dispersion in these exposures, which is partly explained by the extent to which firms operate across countries. We show that portfolios consisting of stocks with low exposures to country shocks achieve substantial variance reduction relative to the global market, both in- and out-of-sample. The shock exposures are thus a stock-selection device for international portfolio diversification.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet